2012
DOI: 10.4048/jbc.2012.15.1.119
|View full text |Cite
|
Sign up to set email alerts
|

Medical and Surgical Treatment of Idiopathic Granulomatous Lobular Mastitis: A Benign Inflammatory Disease Mimicking Invasive Carcinoma

Abstract: PurposeIdiopathic granulomatous lobular mastitis (IGLM) is a rare chronic inflammatory disease of the breast with obscure etiology that mimics invasive carcinoma both clinically and radiologically. The treatment of IGLM remains controversial. The aim of proper management is to use a combination of medical and surgical treatment of this benign condition to achieve a good cosmetic result and low recurrence rate.MethodsA retrospective analysis of 19 patients with IGLM is performed based on the findings of clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
139
1
12

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(157 citation statements)
references
References 11 publications
5
139
1
12
Order By: Relevance
“…Lesions were mammographically undetectable in 6 of 25 females, possibly because of an overlying dense mammary gland pattern observed in most females. With mammography, two patients in our study showed nipple retraction, and one showed skin thickening in the mammary areola, which is more commonly observed in inflammatory breast carcinoma or invasive carcinoma [7][8][9]. The ultrasound manifestations of non-puerperal mastitis varied.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Lesions were mammographically undetectable in 6 of 25 females, possibly because of an overlying dense mammary gland pattern observed in most females. With mammography, two patients in our study showed nipple retraction, and one showed skin thickening in the mammary areola, which is more commonly observed in inflammatory breast carcinoma or invasive carcinoma [7][8][9]. The ultrasound manifestations of non-puerperal mastitis varied.…”
Section: Discussionmentioning
confidence: 65%
“…The majority of patients with non-puerperal mastitis usually exhibit one or several breast masses without any other signs of inflammation. Because it can be very difficult to distinguish these symptoms from breast carcinoma, these patients can easily be misdiagnosed as having an inflammatory breast carcinoma or an invasive carcinoma [7][8][9].…”
Section: Advances In Knowledgementioning
confidence: 99%
“…Many causative agents have been reported to be linked with the condition like -local irritant, oral contraceptive pill, viruses, mycotic and parasitic infections, hyperprolactinemia, diabetes mellitus, smoking, alfa 1 antitrypsin deficiency, autoimmunity have been proposed to explain the etiology of IGM but never proven. [2][3][4][5][6][7] IGM presents most commonly with a unilateral painful, firm, tender, ill defined mass in the breast 7,8 . The lesions may be located in any quadrant of the breast 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Extensive scarring and fistula formation can occur, resulting in unsatisfactory cosmetic results [5]. Medical treatment with corticosteroids prior to surgery significantly decreases the inflammation, which allows for more conservative surgery and reduces the risk of recurrence [5,15].…”
Section: Discussionmentioning
confidence: 99%